Death, Dying and Bereavement - Teggi, Diana (Taylor & Francis, 2026)
While death, dying and bereavement are universal life events, the social conditions under which death takes place are fundamental in shaping how it is experienced by the individual. Bringing together contributors from around the world, this collection of chapters provides sociological insights into death, dying and bereavement. Drawing upon a range of sociological theorists, including Émile Durkheim, Zygmunt Bauman and C. Wright Mills, the book reviews the historical contribution of sociology to the field of thanatology. In doing so, the book challenges individualistic psychological approaches to death, dying and bereavement and demonstrates how sociological approaches can shape, constrain and empower experiences by imbuing them with both collective and individual meaning. Chapter-length case studies explore a wide range of issues, from digital aspects of remembrance and memorialisation and continued threats to liberties that permit life and death decisions to discussions of the impact and likely legacy of COVID-19 and climate change. This collection will be of interest to students and researchers in the social sciences with an interest in societal attitudes towards death and bereavement. Chapter 6 of this book is freely available as a downloadable Open Access PDF at http://www.taylorfrancis.com under a Creative Commons Attribution (CC-BY) 4.0 license.